PM10 exposure interacts with abdominal obesity to increase blood triglycerides: a cross-sectional linkage study. (11th November 2021) - Gaio, Vânia; Roquette, Rita; Monteiro, Alexandra; Ferreira, Joana; Lopes, Diogo; Dias, Carlos Matias; Nunes, Baltazar
Abstract: Background: Blood lipids and glucose levels dysregulation represent potential mechanisms intermediating the adverse cardiovascular effects of ambient particulate matter (PM) exposure. This study aims to estimate the effect of long-term PM10 exposure on blood lipids and glucose levels and to assess the potential mediation and/or modification action of abdominal obesity (AO) (waist-to-height ratio). Methods: Our study was based on 2, 390 participants of the first Portuguese Health Examination Survey (INSEF, 2015) with available data on blood lipids and glucose parameters and living within a 30-km radius of an air quality monitoring station with available PM10 measurements. PM10 concentrations were acquired from the air quality monitoring network of the Portuguese Environment Agency. Generalized linear models were used to assess the effect of 1-year PM10 exposure on blood lipids and glucose levels. An interaction term was introduced in the models to test the modification action of AO. Results: We found an association between PM10 and non-fasting blood triglycerides (TG) after adjustment for age, sex, education, occupation, lifestyles-related variables and temperature but only in participants with AO. Per each 1 µg/m 3 PM10 increment, there was a 1.84% (95% confidence interval: 0.02–3.69) increase in TG. For the remaining blood lipid and glucose parameters, no associations were found. Conclusions: Our study demonstrates that even at low levels of exposure, long-term PM10 exposure interacts with AO to increase blood TG. Our findings suggest that reducing both AO prevalence and PM10 below current standards would result in additional health benefits for the population.